Micro Business Strategies in Facing Capital Problems: Case Study on Pajeng Cokelat Blitar - Dwita Indriyani (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the Indonesian economy, especially in facing economic crises such as the 1998 monetary crisis and the COVID-19 pandemic. MSMEs are at the forefront in creating jobs and contributing to economic growth, even though they face various challenges, including capital problems. This research uses a qualitative approach with a case study type. This research uses primary data collected from interviews with the owner of Pajeng Cokelat. Pajeng Cokelat is a micro business located in Blitar and makes various kinds of processed chocolate to be used as snacks. The owner of Pajeng Cokelat is active in participating in training activities aimed at improving skills both related to marketing and the products produced. The results of this research highlight the government's efforts to overcome capital problems through programs such as People's Business Credit (KUR) and business training. However, increasing financial literacy is needed, especially in the context of sharia finance, to support the sustainable growth of MSMEs. By overcoming these challenges, MSMEs can continue to play a role in driving the national economy.